Influence of functional food composition on the properties of meat mince systems - Strashynskiy, Ihor; Fursik, Oksana; Pasichniy, Vasil; Marynin, Andriy; Goncharov Georgіy (Eastern-European Journal of Enterprise Technologies, 2016)
The priority direction of innovative activity of meat processing enterprises is the production of affordable products of consistent and high quality. Achievement of the set goal is provided by the introduction during developing the mince systems of various food additives that are supposed to replace a considerable part of basic raw materials and to improve its functional and technological properties. The influence of the developed functional food composition on functional-technological and structural-mechanical properties of minces for cooked sausages was studied. It was proved that its introduction to the composition of meat minces increases the indicators of moisture binding ability by 3.5–5 % compared with the control sample. The emulgation ability in the experimental samples increases on average by 5 % and the stability of the emulsion by 22.5 %. This is due to the capacity of protein preparations and hydrocolloids, belonging to the composition, as well as meat proteins to encapsulate drops of fat and retain them throughout the entire process. Determining the influence of the developed functional mix on structural-mechanical properties of minces indicated that the effective viscosity for experimental samples increased on average by 48.5 %, and the indicator of boundary shear stress decreased on average by 40.5 %. The obtained results prove the relevance of substituting a part of meat raw material (up to 30 %) with the developed composition and the improvement of functional-technological and structural-mechanical properties of minces. This will provide for a consistent high quality of the finished products and will increase the effectiveness of production.